Determinants of Physical and Mental Health: A Cross-sectional Study among Rural Adolescent Girls in Bangladesh - Hossain Mahmud; Mia , Md Tuhin; Eva , Esrat Jahan; Naima Ahasan; Chayon Sikder (South Asian Journal of Social Sciences and Humanities, 2025)
Purpose: This study aimed to explore the determinants of physical and mental health changes & problems among rural adolescent girls in Bangladesh. Methods: The study was conducted with 400 participants (adolescent girls) by using convenient sampling technique where Chi-squared tests were used to measure the relationships between physical & mental health determinants of adolescent girls and socio-demographic indicators (age & family income). Findings: This study explored menstruation (72%), breast growing (14%), changes in vocal chores (6%), increasing hair in different parts of body (4%) and changes in size of sexual organs (2%) are the major physical health changes of adolescents. They also acquired some mental health changes e.g., attraction to opposite sex (76%), repeated changes in mood (43%), conscious about dress up (24%), feeling shyness (22%), feeling overly sensitive (8%), conflicting thoughts (13%) and feeling uncertain (11%) etc. In this transition period, adolescent girls also face some physical & mental health problems. Physical weakness (14.2%), headache (82.8), vomiting (0.8%) and depression (54.2%), anxiety (5.5%), mental retired/stress (20.2%, mental distortion/sadness (9%) & fear (9.3%) are the common physical & mental health problems they experienced at this time. Originality: This study reveals the major physical and mental health determinants of adolescent girls with their physical & mental health vulnerabilities. As the most vulnerable group, rural adolescent girls (poor family income) suffer more vulnerability (physical & mental health problems) during their adolescent period.